Phytochemical Screening Of Saponin And Antibacterial Activity Of 96% Ethanol Extract Of Costus Speciosus Against E. Coli And S. Aureus - Prasasty, Vony Intan; Prima, Sylvia Rizky; Damayantie, Wury (Al Makki Health Informatics Journal, 2025)
This study aims to explore the content of secondary metabolite compounds, especially saponins, and to examine the antibacterial activity of ethanol extract of 96% of unsalted pacing leaves (Costus speciosus) against Escherichia coli and Staphylococcus aureus bacteria. Extraction was carried out by maceration method using 96% ethanol solvent, followed by qualitative phytochemical tests to detect the presence of bioactive compounds. The antibacterial activity test was carried out using the disc diffusion method with various concentrations of extracts (5%, 10%, 20%, 40%, and 80%). The results of phytochemical screening showed that the extract contained saponins, alkaloids, tannins, and triterpenoid compounds, while flavonoids were not detected. Antibacterial tests showed that the extract had concentration-dependent increased bacterial growth inhibition activity, with the highest inhibition zone recorded at 80% concentrations against both test bacteria. The Minimum Inhibitory Concentration (MIC) is set at a concentration of 5%, although significant effectiveness is seen starting at concentrations of 10% and above. Based on these findings, it can be concluded that ethanol extract of 96% unsalted pacing leaves has potential as a natural antibacterial agent, which can be further developed as a candidate for local plant-based phytopharmaceuticals. These findings also make a scientific contribution to the utilization of biological resources in supporting alternative medicine in the era of antibiotic resistance.